2016
DOI: 10.1111/vco.12275
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis ofRASandRAFmutation hot spots in canine carcinoma

Abstract: Recent discovery of the BRAF V595E mutation in a variety of canine cancers indicates that mutant BRAF may represent a novel therapeutic target. Presence of RAS mutations is associated with poor tumour response to BRAF inhibition but has not been investigated in BRAF-mutated canine cancers. The aim of this study was to evaluate the mutational status of three RAS genes (HRAS, KRAS and NRAS) in four types of canine carcinoma with and without the BRAF V595E mutation. Novel HRAS mutations were identified in 18% (3/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 54 publications
3
25
0
1
Order By: Relevance
“…We further investigated these results using RFLP assays on all allele (see Appendix S1), consistent with a previous report showing low frequency of this oncogenic mutation in this tumour type. 24 The presence of a somatic HRAS p.Q61R mutation in 94% of the CAA tumour samples analysed in this study, combined with pathogenic similarities between CAA and AM, strongly implicate conserved oncogenic molecular mechanisms between canine and human cancers.…”
Section: Polya+mentioning
confidence: 62%
See 1 more Smart Citation
“…We further investigated these results using RFLP assays on all allele (see Appendix S1), consistent with a previous report showing low frequency of this oncogenic mutation in this tumour type. 24 The presence of a somatic HRAS p.Q61R mutation in 94% of the CAA tumour samples analysed in this study, combined with pathogenic similarities between CAA and AM, strongly implicate conserved oncogenic molecular mechanisms between canine and human cancers.…”
Section: Polya+mentioning
confidence: 62%
“…All OSCC samples had wild‐type HRAS alleles, except case No. 22 which showed an HRAS p.Q61L allele (see Appendix S1), consistent with a previous report showing low frequency of this oncogenic mutation in this tumour type …”
Section: Clinical Information and Hras Mutation Status Of Dogs Includmentioning
confidence: 87%
“…In canine tumors, the BRAF V588E variant has been identified in canine bladder carcinoma (67%), prostatic carcinoma (80%), pulmonary carcinoma (6%), oral squamous cell carcinoma (11%), melanoma (6%) and melanocytoma (17%), glioma (15%), and peripheral nerve sheath tumors (22%; refs. [34][35][36][37][38]. Previous studies exploring canine melanomas have identified the NRAS Q61R mutation in the Jones cell line (33,39) and indicated that canine melanomas have activating NRAS/KRAS/HRAS mutations in 24% of samples (33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies exploring canine melanomas have identified the NRAS Q61R mutation in the Jones cell line (33,39) and indicated that canine melanomas have activating NRAS/KRAS/HRAS mutations in 24% of samples (33). Activating KRAS and NRAS mutations have also been identified in 17% of canine pulmonary carcinomas (38), 58% of acute myelogenous leukemia samples, and NRAS mutations were identified in 14% of acute lymphocytic leukemias (40) while KRAS mutations have been identified in 1 of 14 gastric carcinomas (41), and 4 of 5 pancreatic carcinomas (42). We found activating KRAS or NRAS mutations in 2 of the 6 melanoma lines and 5 of the 33 cell lines including two osteosarcoma cell lines and a bladder carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Die BRAF-Mutation c.1784T>A war in 54,5 % (12) bis 85 % der Übergangszell-und Prostatakarzinome (16)(17)(18), aber nur selten in melanozytären Tumoren, Nervenscheidentumoren, Gliomen und einzelnen anderen Karzinomen des Hundes nachweisbar (16). In den untersuchten hämatopoetischen Tumoren oder Sarkomen wurde die Mutation nicht gefunden (16). Im Gegensatz zum Hund kommt die Mutation des BRAF-Gens beim humanen ÜZCa nur selten (1 %) vor.…”
Section: Introductionunclassified